University course timetabling problem considering day and time pattern - Chompoonoot Kasemset (2020)
© 2019 Inderscience Enterprises Ltd. This study aimed to propose a new formulation for the university course timetabling problem (UCTTP) when a day and time pattern is introduced. The day and time pattern would be set by the university and all assigned courses should follow this pattern. The different points of the proposed formulation would structure the model using starting and ending timeslots instead of a single timeslot to deal with courses with consecutiveness, periodic repeat, and multi-period sessions. To present the effectiveness of the proposed model, three test cases were solved and the results showed that the number of variables and constraints reduced with less computational time. Then, the case study was solved with multiple objectives based on goal programming (GP). The results of the case study show that the number of assignments during the undesirable time was minimised and that the total satisfaction score of all the lecturers was improved.